PENENTUAN SALES MOBIL TERBAIK PADA DEALER MOBIL SISTEM PENDUKUNG KEPUTUSAN WEIGHTED PRODUCT - Yulina Yulina; Aura Marchelita Nugroho (Sienna, 2023)
The automotive industry can make a major commitment to economic growth and job creation. Car sales is one of the key parts of the automotive business that affects the company's results. To face extreme competition, car companies must have the option to select and utilize the best and qualified salespeople. In the face of this challenge, the utilization of a Decision Support System (SPK) can be a powerful tool in selecting the best car sales using the Weighted Product method which is one of the reasonable techniques to determine the best car sales at Gestara car dealerships by considering certain perspectives and criteria. The criteria used in this study include Attendance, Friendliness, Discipline, Politeness, Leadership and Target. This research is expected to help the company in providing references to develop further services, improve sales performance, and understand the Weighted Product method.